2018
DOI: 10.1101/497792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly reproducible 16S sequencing facilitates measurement of host genetic influences on the stickleback gut microbiome

Abstract: Multicellular organisms interact with resident microbes in important ways, and a better understanding of host-microbe interactions is aided by tools such as highthroughput 16S sequencing. However, rigorous evaluation of the veracity of these tools in a different context from which they were developed has often lagged behind. Our goal was to perform one such critical test by examining how variation in tissue preparation and DNA isolation could affect inferences about gut microbiome variation between two genetic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Frozen guts were weighed, rapidly thawed, and samples were immediately processed for DNA extraction using a modified Dneasy Blood and Tissue Kit protocol [42]. Guts were transferred to preheated Qiagen PowerBead Solution in QIAmp PowerFecal DNA Kit garnet bead lysis tubes and homogenized on a FastPrep120.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen guts were weighed, rapidly thawed, and samples were immediately processed for DNA extraction using a modified Dneasy Blood and Tissue Kit protocol [42]. Guts were transferred to preheated Qiagen PowerBead Solution in QIAmp PowerFecal DNA Kit garnet bead lysis tubes and homogenized on a FastPrep120.…”
Section: Methodsmentioning
confidence: 99%
“…We demultiplexed 16S reads and performed quality filtering, merging, denoising, and taxonomy classification using tools from QIIME 2 v2018.8.0 40 , generally according to the methods described in Small et al 2019 29 . Briefly, we used demux ( emppaired ), vsearch ( join-pairs ), quality-filter ( q-score-joined ), and deblur ( denoise-16S ) to define amplicon sequence variants (ASVs).…”
Section: Methodsmentioning
confidence: 99%
“…Gut DNA isolations were standardized to 20ng/µl and submitted to the University of Oregon Genomics Core Facility (GC3F) for 16S rRNA (V4 region) amplicon library construction and sequencing (paired-end 150 nt reads) in a single lane on an Illumina HiSeq 4000 (See Supplementary Methods and Small et al 2019) 29 . Also sequenced were three negative control libraries, generated from a no-tissue extraction sample and two no-PCR-template reactions.…”
Section: Library Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are not many studies de ning the effects of the host genome on intestinal microbiota composition in sh. However, it has been demonstrated that there is a clear correlation between sh genotype and intestinal microbial communities [56][57][58][59][60]. Yet, to date, there is no information on the genome ´ intestinal microbiota interaction of genetically selected gilthead sea bream and how this can affect diet plasticity, health and disease resistance.…”
Section: Introductionmentioning
confidence: 99%